EFEKTIFITAS PENGGUNAAN TULISAN SINGKAT BRAILLE DALAM MENINGKATKAN KECEPATAN MENULIS BAGI ANAK TUNANETRA - Elsa Rahmadia; Ganda Sumekar; Fatmawati Fatmawati (Universitas Negeri Padang, 2012)
The research was motivated by the existence of blind children who are sitting in class IX, but still slow in writing letters Braille compared with sighted friends. The study aims to find effective brief use of Braille is associated with a single word in increasing the speed of writing for children blind class IX in SMPN4 Payakumbuh.This type of research is an experiment in the form of Single Subject Research (SSR) with the A-B-A design. Variable's researchers are engaged in the writing speed and variable free el is the use of Braille sort writing. Data collection techniques through observation, interviews, and tests. Analysis techniques in this study is descriptive percentages.This study finds on sessions baseline observations of the first session until the tenth child's ability to landscape, change data which is about 18%, 19.6%, 20%, 22.8%, 23.2%, in the intervention condition (B), Increased continue from 40% up to 42%, and the children are getting good value. At baseline (A2) do as much as ten times of observation, the ability of the child 43% to 50%. It can be concluded that the use of short writing Braille effective in increasing the speed of writing for the blind boy.Researchers suggest that teachers in teaching writing to children with visual impairments to use intervention brief Braille for blind children, especially class IX in SMP 4 Payakumbuh so as to enhance the capabilities of blind children in the speed of writing